Investigation on Tensile Behaviour of Different Weld Joints through Taguchi Approach - Shoaib Kamal; V. Parthiban; G. Puthilibai; M. Thirumal Azhagan; Neel Kamal; T. S. Senthil; Simon Yishak (Advances in Materials Science and Engineering, 2022)
Friction stir welding is a dependable method of joining metals and other materials. Relatively joint configuration-specific welding process parameters have not yet been tuned. This work is concerned with the Taguchi orthogonal arrays to perform an analysis of variance. In this study, FSW joint configurations of AA6262-T6 Al alloy, such as butt, lap, and T joints, were studied for optimization. An orthogonal array of welds was selected using the Taguchi method. After the welds were constructed, the ultimate tensile strength of each joint was examined for statistical optimization. The lack of parameter optimization studies for butt, lap, and T joints prompted this research to fill the void. As a result, each joint arrangement must be optimised for mechanical properties and a set of parameters must be developed.